2014
DOI: 10.1155/2014/967373
|View full text |Cite
|
Sign up to set email alerts
|

A New Method of Improving Low-Speed Performance of Variable Speed Hydraulic Systems: By Leaking Parallel Valve Control

Abstract: Aiming at improving low-speed performance of variable speed hydraulic systems, the leaking parallel valve control is applied to the system during low-speed period. This method increases system damping ratios by increasing leakage controlled by the valve. In addition, the increase of damping ratios just compensates the reduction of damping ratios due to the friction negative slop, which helps to improve low-speed stability and achieve lower critical speed. In the whole process of closed loop control, the system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…When the PDV is closed, and Q l0 , Q r0 , K cl and K cr are zero in Equations (11) and (12), the LPVC mode and RPVC mode will switch to the VSPC mode, and its open-loop dynamic equation is [1,2,20]…”
Section: Valve-pump Parallel Control Motor Linkmentioning
confidence: 99%
See 2 more Smart Citations
“…When the PDV is closed, and Q l0 , Q r0 , K cl and K cr are zero in Equations (11) and (12), the LPVC mode and RPVC mode will switch to the VSPC mode, and its open-loop dynamic equation is [1,2,20]…”
Section: Valve-pump Parallel Control Motor Linkmentioning
confidence: 99%
“…Figure 6 also shows that the response in the RPVC mode will be further improved by raising the supply pressure P s . As known, the open-loop gain increase will accelerate the system response, and open-loop gains K 3 are proportional to flow gains K vr according to Equation (20) and the flow gain of PDV in the replenishing status is given by K vr ¼ C sv ffiffiffiffiffiffiffiffiffiffiffiffiffiffi ffi P s À P h p in Equation(6), hence the raising P s will increase K vr and K 3 and then will accelerate the dynamic response. Figure 7 shows influences of load variation on the total leakage coefficient when keeping the inputs of pump and valve constant (u p = 6V, u l = ¡4V, u r = 4V).…”
Section: In Open-loop Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to improve the pump control system's performance while keeping its high energy savings, some researchers combined the valve control and pump control methods [11]. Zhao et al [12] put forward a new control mechanism of valve-pump paralled variable structure control which could be accommodated between valve control and pump control to meet the control requirements, and concluded that the overall characteristic of the variable speed pump control system could be significantly improved.…”
Section: Introductionmentioning
confidence: 99%
“…However, almost all hydrostatic pumps have high friction losses, strong wear and often also high volumetric losses at speeds below 500 rpm. While there have been efforts to work around these minimum speed limitations of pumps, they typically depend on introducing new throttling losses via a variable leakage path [5,6].…”
Section: Introductionmentioning
confidence: 99%